Simulator of Organic Rankine Cycle - Eghan Dharmabudhi Pramodana; Shabrina Hapsaryta Aufari (Pusat Teknologi Instrumentasi dan Otomasi (PTIO) - Institut Teknologi Bandung, 2017)
A program package was developed to simulate the operation of an organic Rankine cycle system. The brine ejected from a geothermal plant usually is directly injected back through the injection well into the ground. The brine, however, with a flow rate of 3.125 kg/s and temperature range of 150°C to 170°C is considered to still contain significant amount of useful heat. The waste heat from the brine may be utilized to generate power using the Rankine cycle with working fluid of organic substances. Several organic substances such as R227ea, R124, R236ea, and R245fa are suitable to be uitilized as the working fluid. The simulation program package was developed using MATLAB that has been coupled with CoolProp. It can be used for simulation study of the thermal efficiency and working effectiveness of the system.